Workability-optimized reactive polymer composition
Silane-modified polypropylene copolymers with controlled properties address high viscosity and tackifier reliance in adhesives, enhancing workability and bonding on diverse substrates through metallocene catalysts, achieving flexible and heat-resistant adhesives with reduced resin use.
Patent Information
- Application Number
- JP2023578720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-01
- Filing Date
- 2022-06-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-06-13
AI Technical Summary
Existing silane-modified polyolefin adhesives face issues with high viscosity, requiring large amounts of tackifiers for workability, limited temperature flexibility, and poor bonding properties on various substrates, especially polar surfaces, due to chain degradation and low functionalization rates.
Silane-modified polypropylene copolymers with specific silicon content, melt viscosity, and enthalpy of fusion, combined with metallocene catalysts, to achieve balanced mechanical and adhesive properties without excessive tackifiers, ensuring flexibility and high heat resistance.
The solution provides hot melt adhesives with improved workability, cohesion, adhesion, and heat resistance, particularly on polar substrates, with reduced resin use, maintaining flexibility and stability across a wide temperature range.
Smart Images

Figure 0007602072000001 
Figure 0007602072000002 
Figure 0007602072000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a silane modified polypropylene copolymer having a silicon content of 1-5 wt.%, a melting enthalpy of 20-35 J / g, and a melt viscosity at 170° C. of 500-4500 mPas. The present invention further relates to a workability optimized reactive hot melt adhesive formulation comprising said silane modified polypropylene copolymer, and the use of said hot melt adhesive formulation for bonding various substrates. The present invention also relates to a process for the preparation of said silane modified polypropylene copolymer. [Background technology]
[0002] Semicrystalline poly-α-olefins are often used as adhesive raw materials in a variety of applications, ranging from the hygiene sector through laminating and packaging adhesives to structural bonding, as well as for use in wood processing.
[0003] By grafting with crosslinkable agents, e.g. alkoxysilanes, it is possible to modify the cohesion, adhesion, mechanical stability and heat resistance of unmodified poly-α-olefins, since the crosslinking of polymer chains with each other changes the polymer properties, and the grafted alkoxysilanes also allow the covalent incorporation of reactive surface groups (e.g.: -OH) into the adhesive bonds.
[0004] Free radical induced grafting of semicrystalline poly-α-olefins with silane groups leads to chain degradation of the ungrafted polymer, often resulting in very low degrees of functionalization and forming graft products with very waxy properties (e.g. WO 89 / 11513), which are not suitable for stable adhesion.
[0005] This also applies to free radical induced grafting reactions of polypropylene or propylene rich copolymers, in which chain degradation is also known to occur, which reduces the molar mass (melt viscosity) of the polymer. Corresponding polymers with a high degree of functionalization therefore necessarily have a very low molar mass / melt viscosity and are not suitable for application in many fields.
[0006] Furthermore, cross-linking of degraded polymer chains by silane groups can result in changes in mechanical properties, in extreme cases resulting in hard, high-strength materials with low brittle temperatures.
[0007] WO2007008765, Dow, describes the use of low viscosity silane-grafted poly(ethylene-co-1-olefin) polymers as adhesive raw materials, disclosing that the polymers used contain at least 50 mol % ethylene and have a polydispersity index of 1-5, preferably 1-3.5. They exhibit low melt viscosities of 2,000 to 50,000 cP at 177°C. The 1-olefin comonomers include many higher 1-olefins such as, for example, 1-hexene and 1-octene. Silane-grafted polymers have low fracture temperatures in PAFT and SAFT analysis. The use of polyolefins with high ethylene content implies the presence of long ethylene blocks in the polymer. This very often results in poor wetting and bonding properties on the surfaces of many plastics, leading to bonding problems. Furthermore, long polyethylene sequences tend to crosslink with peroxides, which makes gel formation inevitable. The ungrafted base polymer has a relatively low molar mass and melt viscosity of 50,000 cP or less at 177°C.
[0008] Similarly, the use of crystalline and semi-crystalline poly(propylene-co-1-olefin) polymers, which are also said to be suitable for grafting, is described. These have a propylene content of at least 50 mol%, a melt viscosity of preferably 50000 cP at 170° C. (before and after grafting) and a polydispersity index of 1 to 3.5. The crystallinity is reported to be between 2 and 60% (i.e., between 3 and 100 J / g). However, there are no examples of these polypropylene-based copolymers identified as preferred. No work has been done on polymers with melting enthalpies between 20 and 35 J / g and viscosities between 500 and 4500 mPas. Thus, the document does not describe specific combinations of features or advantageous processing and bonding properties resulting therefrom.
[0009] EP 0827994 (Huels) describes the use of silane-grafted amorphous poly(α-olefins) as moisture-crosslinkable adhesive raw materials or adhesives. The base polymers used are atactic polypropylene (aPP), atactic poly(1-butene) or preferably copolymers or terpolymers of C4-C10 α-olefins (0-95 wt%), propene (5-100 wt%) and ethylene (0-20 wt%). The silane-modified APAO terpolymers described in the examples have a softening point of 98°C, a weight average molecular weight of 38,000 g / mol and a melt viscosity of 6000 mPas. The grafting reduced the PDI by more than 35% and the reduction in viscosity was 88%. There is no detailed discussion of the processing properties together with the mechanical properties.
[0010] DE 10338344 A1 (Clariant) relates to semicrystalline polyolefin homopolymers or copolymers which are free-radically modified with silane compounds and have a viscosity, measured at 170°C, of 10 to 50,000 mPas and a heat of fusion of more than 10 J / g. The examples disclose polyolefins having a melt viscosity of less than 1000 mPas at 170°C, a drip point of more than 110°C and a heat of fusion of at least 60 J / g. They are suitable as constituents of hot-melt adhesive formulations. There is no disclosure of a combination of low melt viscosity and a heat of fusion of 20 to 35 J / g. The silane-modified crystalline polyolefin waxes are produced by metallocene catalysis and have a high propylene content.
[0011] In the case of hot melt adhesive formulations containing silane modified polyolefins, the bonding process has two stages. To avoid processing problems and ensure easy application, those skilled in the art are looking for hot melt adhesive formulations with low viscosity so that the hot melt adhesive can be applied at relatively low temperatures under pressure. As soon as the adhesive is applied, crosslinking begins, which increases the viscosity and enhances the cohesion of the bond, which is believed to ensure the mechanical stability of the final bond.
[0012] However, it should be considered here that very low viscosity products with a viscosity of 8000 mPas or less usually have disadvantages in mechanical properties such as modulus, strength, and elongation at break, because very short chain lengths lead to less entanglement from the less polymer, and the product is more likely to have waxy properties. Furthermore, very short chain lengths lead to rapid embrittlement of the material upon crosslinking, because the short interlinked polymer chains have low flexibility. Therefore, the prior art does not teach the use of very low viscosity base polymers, and recommends the use of relatively high amounts of tackifiers in conjunction with relatively high viscosity silanized polyolefins.
[0013] Tackifiers affect the viscosity and initial adhesion of the bonding adhesive and are often resins, e.g., low molecular weight products from C5 or C9 streams in petroleum processing, often contain aromatic compounds, and usually have a glass transition temperature above room temperature.
[0014] Thus, the addition of resins to hot melt adhesive formulations increases the glass transition temperature of the formulation and therefore renders such hot melt adhesives less flexible at low temperatures, limiting the temperature range over which the hot melt adhesives can be used.
[0015] WO2010018027 (Evonik) discloses silane-modified polypropylene copolymers and terpolymers with high functionalization, with 2.5 wt% or less of poly(ethylene) triads, enthalpies of fusion between 9 and 20 J / g and xylene solubility above 96 wt%, with the terpolymers containing ethylene and 1-butene obtaining the best results. Many exemplary formulations are mentioned for various adhesive bonds containing these modified polyolefins. These formulations give relatively good mechanical stability after bonding, but relatively large amounts of tackifier are required to ensure good processing properties and sufficient initial tack. The lowest percentage of modified polyolefin in the formulation is reported as 24.7 wt% in the exemplary formulation for edge bonding. All other examples contain 30 wt% or more.
[0016] Furthermore, Patent Document 4 (WO2010018027A1) claims that peroxide-induced grafting reaction further reduces the polydispersity of the polymer used, and the modified polymer has a polydispersity index of less than 3.5, which leads to various disadvantages, particularly in terms of working properties.Furthermore, this document teaches that the use of a relatively low molecular weight base polymer generally leads to a relatively low functionalization rate.
[0017] Patent document 5 (EP3287276A1, Sika) describes a hot melt adhesive composition comprising a silane-modified poly-α-olefin that is solid at 25°C, an unmodified amorphous C3 / C2 copolymer wax having a softening temperature of less than 120°C, and a paraffin wax having a softening point of 80-130°C.
[0018] Patent document 6 (WO2009133093, Sika) discloses a hot melt adhesive composition with long open time, comprising a silane-modified poly-α-olefin that is solid at 25° C. and a plasticizing resin with a melting or softening point of 10-40° C. An example formulation contains 65% by weight of silane-modified poly-α-olefin. The proportion of all silane-grafted poly-α-olefins is more than 50% by weight, preferably 60% to 90% by weight. [Prior art documents] [Patent documents]
[0019] [Patent Document 1] WO2007 / 008765 [Patent Document 2] DE10338344 [Patent Document 3] WO2010018027 [Patent Document 4] WO2010018027 [Patent Document 5] EP3287276 [Patent Document 6] WO2009133093 Summary of the Invention [Problem to be solved by the invention]
[0020] Therefore, it is usually necessary to add relatively large amounts of tackifiers and low viscosity components to silane modified adhesive formulations to establish workability and initial strength of the bond. Without these additions, silanized polyolefins have high viscosities, which limit the scope of use and require additional work-related and material-specific issues to be considered when formulating adhesives. Therefore, adhesive formulations are required to meet a balanced and wide range of use, minimize the proportion of functional additives, and consist of as few components as possible. Therefore, there was a need for functionalized polyolefins as and for hot melt adhesives, which, due to their improved material properties, can be worked and applied without the use of many resins or tackifiers, even at low temperatures (below 170°C), and yet have sufficient initial adhesion and flexible and stable bonds as well as high heat resistance. [Means for solving the problem]
[0021] Surprisingly, it has been found that silane-modified polypropylene copolymers having a silicon content of 1-5% by weight based on the total weight of the modified polymer, a melt viscosity at 170°C of more than 500 mPas and less than 4500 mPas, and a melt enthalpy of more than 20 J / g and less than 35 J / g, preferably more than 20 J / g and less than 30 J / g, as hot melt adhesives or as components of hot melt adhesive formulations, impart very advantageous properties to the formulations and improve the workability. Copolymer in the present invention refers to a polymer composed of two or more different monomer units. The silane-modified polypropylene copolymers contain one or more monomers selected from the group consisting of ethylene and 1-butene as further monomers, preferably being binary copolymers, with propylene and ethylene being particularly preferred as comonomers.
[0022] Silane modified polypropylene copolymers provide both very good workability and very good mechanical properties of the bond, which can be qualitatively and quantitatively expressed as good cohesion, adhesion, heat resistance and elongation at break of the hot melt adhesive. In order to meet the same requirements of hot melt adhesive properties as for conventional formulations in terms of heat resistance, cohesion, elongation at break, etc., the proportion of reactive silanized components in the formulation should be relatively low. The advantageous properties of hot melt adhesives are especially manifested on polar substrates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The unmodified polypropylene copolymer is modified by grafting. Possible side reactions during the grafting process, among others, scission of the grafted polymer chains, therefore grafting and modification are considered synonymous in the present invention.
[0024] The silane-modified polypropylene copolymer has a silicon content of 1-5 wt%, a melt viscosity at 170° C. of more than 500 mPas and less than 4500 mPas, a melt enthalpy of more than 20 J / g and less than 35 J / g, preferably more than 20 J / g and less than 30 J / g, and the melt viscosity is preferably 10-50% of the viscosity of the original unmodified polypropylene copolymer. Such a percentage change in melt viscosity allows for particularly easy workability, together with good mechanical stability, due to the appropriate degree of crosslinking.
[0025] The silane to be grafted preferably has an olefinic double bond and one to three alkoxy groups directly bonded to the silicon atom. In particular, the one or more silanes are selected from the group consisting of vinyltrimethoxysilane (VTMO), vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-methacryloyloxypropyltrimethoxysilane (MEMO; H2C=C(CH3)COO(CH2)3-Si(OCH3)3), 3-methacryloyloxypropyltriethoxysilane, vinyldimethylmethoxysilane, and / or vinylmethyldibutoxysilane. The silane is most preferably vinyltrimethoxysilane.
[0026] In order to establish the desired mechanical properties, it is advantageous for the polypropylene copolymer backbone of the silane modified polypropylene copolymer to have a weight average molecular weight, measured according to ISO16014-1, of more than 10,000 g / mol and less than 30,000 g / mol, preferably more than 10,000 g / mol and less than 20,000 g / mol; within this molecular weight range, the polymer chains are sufficiently functionalized and therefore can be stably crosslinked, but still have sufficient flexibility.
[0027] Silane-modified polypropylene copolymers preferably have a polydispersity index (PDI) of less than 2.5. The PDI is preferably increased as a result of grafting, being at least 20% higher relative to the non-grafted polymer. This change in PDI as a result of grafting is clearly established only in the case of silane-modified polypropylene-based copolymers, where the free radical-induced chain decomposition reduces the viscosity sufficiently, but nevertheless to a small enough extent to allow subsequent crosslinking to ensure both high flexibility and sufficient strength of the bonds. This increase in PDI was completely surprising, since usually free radical-induced chain decomposition leads to a decrease in PDI.
[0028] The silane-modified polypropylene copolymer preferably has a softening point of 85 to 95° C. The silane-modified polypropylene copolymer having a softening point within this range has sufficiently good properties in terms of both heat resistance and workability.
[0029] Further, the silane modified polypropylene copolymer preferably has a viscosity of 0.900 g / cm 3 It has a density greater than
[0030] The silane modified polypropylene copolymer preferably has a mm triad of propylene fraction within a region of 90 mol % or less and a rr triad of at least 5 mol %. The silane modified polypropylene copolymer having the microstructure exhibits desirable working and mechanical properties.
[0031] In a preferred embodiment, the silane modified polypropylene copolymer is produced using a metallocene catalyst.
[0032] In a preferred embodiment, the unmodified reactants of the silane modified polypropylene copolymer contain at least 60 mole percent propylene, more preferably 70-90 mole percent propylene. Within this range, the comonomer content is sufficient to prevent embrittlement of the material, but not so high that the ethylene content is too high, resulting in poor bonding properties.
[0033] The native reactants are 13 The propylene content, as determined using C-NMR, is preferably at least 60 mole percent.
[0034] The present invention further provides a method for producing a silane-modified polypropylene copolymer according to any one of claims 1 to 8, comprising the steps of: (a) supplying a polypropylene copolymer; (b) adding a grafting component and a free radical initiator; and (c) evaporating excess monomer, wherein the grafting reaction results in a melt viscosity that is 50 to 90% lower than the viscosity of the original unmodified polypropylene copolymer, and a PDI that is at least 20% higher.
[0035] In the method of the present invention, the unmodified polypropylene copolymer used has a melt viscosity, measured at 170°C in accordance with DIN 53019, of 500 to 7000 mPas, preferably 700 to 5000 mPas, more preferably 800 to 4000 mPas, and a melting enthalpy, measured in accordance with ISO 11357-3, of 30 to 55 J / g, preferably 30 to 50 J / g, more preferably 30 to 45 J / g.
[0036] The present invention further provides a hot melt adhesive formulation comprising the silane modified polypropylene copolymer of the present invention and one or more base polymers selected from the group consisting of unmodified polyolefins and unmodified thermoplastic styrene block copolymers (TPE-S), wherein the silane modified polypropylene copolymer and the base polymer are at least 50 wt. % and the silane modified polypropylene copolymer is not more than 30 wt. %, based on the total weight of the hot melt adhesive formulation.
[0037] The unmodified polyolefin is preferably a crystalline or semi-crystalline polyolefin, or an amorphous polyolefin (APAO), an ethylene vinyl acetate copolymer (EVA), and a polyisobutylene (PIB), where the polyolefin is more preferably formed from a C3 / C2 copolymer, and the unmodified styrene block copolymer is preferably SBS, SEBS, SEPS, SEEPS, and MBS.
[0038] The hot melt adhesive formulation preferably has a melt viscosity, measured at 170° C. according to DIN 53019, of less than 5000 mPas and a tensile strength of at least 4 MPa; a hot melt adhesive having these properties constitutes an optimum between workability and mechanical stability.
[0039] The hot melt adhesive formulations of the present invention may contain synthetic and / or natural resins, in particular tackifying resins, synthetic and / or natural oils, inorganic and / or organic, synthetic and / or natural polymers, which may be electrically conductive or insulating.
[0040] In particular, the hot melt adhesive formulations of the invention comprise tackifying resins (tackifiers) which are used to adjust certain properties of the adhesive layer, in particular the tackiness and / or adhesion, the flow and creep properties of the adhesive layer and / or the adhesive viscosity, to specific requirements. These may be natural and / or synthetic resins. In the case of natural resins, these contain abietic acid as the main component (e.g. rosin). Furthermore, the resins may be terpene or polyterpene resins, petroleum resins and / or coumarone-indene resins, in particular the so-called C5 resins and / or C9 resins and / or copolymers of C5 / C9 resins.
[0041] The proportion of tackifier in the hot melt adhesive of the present invention is 35% by weight or less, more preferably 1-30% by weight, and particularly preferably 3-20% by weight, based on the total weight of the formulation. This is because a small amount of resin can provide a hot melt adhesive with a viscosity excellent in workability, and the amount of this in the hot melt adhesive of the present invention is sufficient to ensure sufficient initial adhesion.
[0042] The hot melt adhesives of the present invention may contain further components required to achieve specific properties, such as deformability, adhesion, processability, crosslinking rate, crosslinking density, (melt or solution) viscosity, strength, crystallization rate, tack, storage stability, etc.
[0043] More preferably, the hot melt adhesive formulation comprises, based on the total weight of the hot melt adhesive formulation, 40-80 wt. % of the base polymer, 10-30 wt. % of the polypropylene copolymer, and 10-30 wt. % of the tackifier. Formulations having these weight proportions provide hot melt adhesives with an optimal manifestation of the desired properties and a particularly balanced property profile.
[0044] In a particular embodiment of the present invention, the proportion of the further component is particularly preferably 10% by weight or less.This has the advantage that the material properties of the adhesive formulation are essentially the material properties of the polymer of the present invention used.Such adhesive formulations can be produced with a very low level of complexity.
[0045] Said further components may be crosslinking promoters, in particular silanol condensation catalysts, inorganic and / or organic fillers which may be selectively conductive or insulating, inorganic and / or organic pigments which may be selectively conductive or insulating, inorganic and / or organic, synthetic and / or natural fibers which may be selectively conductive or insulating, inorganic and / or organic stabilizers, and / or inorganic and / or organic flame retardants.
[0046] In another embodiment, the silane modified polypropylene copolymer or the hot melt adhesive formulation comprises 0.1 to 1 wt. % of crosslinking promoter, based on the total weight of the mixture of the silane modified polypropylene copolymer and the crosslinking promoter or the hot melt adhesive formulation, which is particularly preferred when the polymer of the invention is used in adhesive bonds that achieve their maximum durability within a short time after bonding.
[0047] Suitable crosslinking promoters are in particular Brönsted and / or Lewis acids, although a large number of chemical compounds can be used, such as, for example, acetic acid, itaconic acid, zinc(II) acetate, cadmium acetate, zinc oxide, zinc stearate, zinc(II) chloride, tin(IV) chloride, dibutyltin oxide, dibutyltin dilaurate, bismuth citrate, bismuth(III) oxide, bismuth titanate, tetrabutylgermanium, tetrabutyltin, titanium boride, titanium(IV) oxide, titanium acetylacetonate, tributyl titanate, magnesium chloride, magnesium(II) chloride, zinc acetylacetonate, zinc methacrylate, zinc niobate, tin(II) oxide, tin(IV) oxide, zirconium(IV) acetylacetonate, zirconium(IV) oxide and / or zirconium(IV) silicate.
[0048] Test Method The polyolefins listed were characterized according to the specifications given. Characterizations without specifications were performed as described.
[0049] The weight average and number average molecular weights of the copolymers (M w and M. n ) was measured in 1,3-ortho-dichlorobenzene by PP calibration. The measurement was performed by gel permeation chromatography at 135 °C according to ISO 16014-1.
[0050] The softening point was measured according to ASTM D3104. Density was measured according to ISO1183-3:1999.
[0051] Melt viscosity is measured according to DIN 53019 as follows: the test liquid is placed in an annular gap between two coaxial cylinders, one of which rotates at a constant speed (rotor) and the other is stationary (stator). The speed and torque required to overcome the frictional resistance of the liquid in the annular gap are measured.
[0052] Using the geometric dimensions of the system and the measured torque and velocity values, the shear stresses and velocity gradients present in the liquid can be calculated. The standard describes standard flow diagrams for measuring the flow characteristics of Newtonian and non-Newtonian liquids in a rotational viscometer with concentric cylinders by prescribing certain geometrical proportions. Since the reactants and silane-modified products are structurally viscous liquids, the dynamic viscosity was measured three times at 170°C with different shear rates and the average value was obtained (shear rate 1: 192 1 / s, shear rate 2: 318 1 / s, shear rate 3: 532 1 / s).
[0053] The enthalpy of fusion and the glass transition temperature were determined by differential scanning calorimetry (DSC) according to ISO 11357-3 and ISO 11357-2. The enthalpy of fusion, the glass transition temperature and the melting range of the crystalline components are determined via DSC from the second heating curve at a heating rate of 10 K / min. The turning point of the heat flow curve was taken as the glass transition temperature. The modified polymers are always analyzed in the uncrosslinked state and without additional additions; a blanket of dry protective or inert gas (e.g. nitrogen, argon, etc.) during the measurements is advisable.
[0054] The polydispersity index PDI is the weight average molecular weight M w and number average molecular weight M n It is calculated from the quotient of and defined in accordance with standard ISO 16014-1.
[0055] The silicon content was confirmed by adsorption photometry using a Perkin-Elmer Lambda35 photometer. For this purpose, the analytical samples are digested as follows: 0.1-0.15 g of polymer, depending on the Si content, is weighed into a platinum crucible and 0.5 ml of concentrated sulfuric acid is added. The liquid is evaporated on a hot plate and then ashed in a muffle furnace at 600 °C for 1.5-2 h to produce sulfate ash. The sulfate ash is subsequently digested in a flame with a minimum amount of sodium carbonate, leached from the platinum crucible with Millipore water and rinsed into a 100 ml plastic standard flask.
[0056] To photometrically measure the silicon content of the samples thus digested, 10 ml of the digested solution are pipetted into a 50 ml plastic standard flask and 5 ml of 2 M sulfuric acid are added to adjust the pH. 10 ml of molybdate reagent is then added and the aqueous solution is made up to 50 ml with Millipore water.
[0057] Before the measurements, the photometer is calibrated by the following method: A calibration series with concentrations of 0, 1, 2, 4 and 5 mgSi / l from the stock solutions is pipetted into a 50 ml flask. 5 ml of 2 M sulfuric acid is added to adjust the pH. Then 10 ml of molybdate reagent is added and the calibration solution is transferred into the corresponding cuvette. After 2-10 min in the photometer, calibrate with the samples of the calibration series at a wavelength of 400 nm. To verify the calibration, an external control standard with a concentration of 5 mgSi / l is prepared in the same way and measured in the photometer.
[0058] The sample aqueous solution to be measured for silicon content is transferred to a cuvette and measured in a photometer at a wavelength of 400 nm after 2 to 10 minutes.
[0059] The adhesive strength was determined according to DIN EN 1465 as the adhesive shear strength in a lap shear test. All specimens used are cleaned and de-dusted before preparation of the specimens. All plastic and glass specimens are additionally degreased with a suitable cleaning agent before sample preparation. The specimens are then glued according to DIN EN 1465. All specimens prepared in this way are stored in a climate-controlled room at a temperature of 20°C and a humidity of 50% for 14 days before use. This allows, for example, for wood specimens, for the moisture content to be homogenized. In this way, idiosyncratic effects caused by an increase in moisture content, for example, in the case of hydrophilic or hydrolysis-sensitive polymers, are excluded or minimized.
[0060] The cohesion was determined as the tensile strength in a tensile test according to DIN EN ISO 527-3.
[0061] Propylene content and PP triads are 13 C-NMR was used to measure the cleavage and quantification was performed by integration of characteristic signals: 13 C-NMR spectra were recorded using a Varian Mercury-VX400 (9.4 Tesla) NMR spectrometer with a 5 mm sample head (nuc4, C sensitive). 13C-NMR measurements (Larmor frequency: 100.62 MHz) were performed under quantitative conditions, i.e., using an inverse gated pulse sequence. Other parameters were: spectral width 25 kHz, recording time 1.3 s, relaxation delay 20 s, number of scans about 4000, excitation angle 90°, measurement temperature 80 °C. For this purpose, in each case about 50 mg of EP copolymer was dissolved and homogenized in 0.7 ml of solvent (20% C6D6 / 80% 1,2,4-trichlorobenzene). The proportion of triads was calculated according to Markov statistical probability analysis adapted to PP / PE copolymers.
[0062] The elongation at break of the hot melt adhesives according to the invention was determined according to ISO 527, except that non-standard specimens were used in each case, which were produced by melt pressing and whose dimensions differed from the standard specimens. The specimens used for the strength and elongation at break measurements had the following dimensions: total length 50 mm, width in the narrow part 3.3 mm, width at the ends 7 mm, length of the narrow parallel part 25 mm, thickness 1 mm.
[0063] The elongation at break corresponds to the tensile strength at break and is determined by tensile testing according to ISO 527. What is measured here is the force per unit area (reported in MPa) required to break the test specimen. With the exception of the test specimens, the tensile tests were carried out according to standard ISO 527. EXAMPLES
[0064] The present invention will now be described in detail with reference to the following examples.
[0065] For the grafting of the polypropylene copolymers produced with the metallocene catalysts listed in columns 2 and 3 of Table 1, 500 g of the respective polypropylene copolymer were in each case melted under a nitrogen blanket in a glass apparatus equipped with a stirrer system, an internal thermometer and a distillation system. Columns 4 to 6 are the values for non-grafted comparative polyolefins from the prior art.
[0066] [Table 1]
[0067] At a temperature of 160° C., over the course of 3 hours, 50 g of trimethoxyvinylsilane (10% based on the amount of polymer used) were metered in continuously from a metering funnel, while 10 g of di-tert-butyl peroxide were added continuously from a second dropping funnel. After the end of the metered addition, a further 1.1 g of di-tert-butyl peroxide was added to the reaction mixture, and the mixture was reacted at 160° C. for 1 hour.
[0068] Subsequently, a vacuum (approximately 30 mbar) was applied to distill off the volatile components. After approximately 30 minutes, the mixture was depressurized to normal pressure by introducing nitrogen.
[0069] The properties of the resulting modified products are given in columns 2 and 3 of Table 2. Columns 4-6 are data for non-grafted comparative polyolefins from the prior art.
[0070] [Table 2]
[0071] Manufacture of hot melt adhesive formulations and bonding of various substrates The hot melt adhesive formulations of the present invention were prepared by hot melt mixing (about 180°C) using a propeller stirrer to prepare a molten mixture of the silane modified polypropylene copolymer and the additional components in the amounts specified in Table 3.
[0072] [Table 3]
[0073] In the examples 2, 5 and 8 of the present invention, it is shown that in the hot melt adhesive formulation, when the formulation has a low viscosity, it is possible to improve the cohesion (tensile strength), elongation at break, heat resistance, and adhesion (lap shear strength) of various substrates, especially on wood. When silane-modified polypropylene copolymer is used as the only component of the hot melt adhesive, the silane-modified component of the present invention is clearly superior to the comparative examples on wood. Even on polypropylene (PP) and ABS, the single component of the present invention shows good adhesion and is clearly improved in terms of cohesion compared to comparative examples 1 and 3.
[0074] These properties, already favorable in the single components, show their full potential in the formulation. Examples 5 and 8 of the present invention, which have the same concentration of reactive components in the formulation, show much lower viscosity, which clearly improves and expands the user's workability range, and also show much higher heat resistance and clear improvements in cohesion, adhesion and elongation at break than Comparative Examples 4, 6, 7 and 9.
Claims
1. Silane-modified polypropylene copolymers containing ethylene and / or 1-butene as comonomers, a photometrically determined silicon content of 1-5 wt.-%, based on the total weight of the polymer, a melt viscosity measured at 170° C. according to DIN 53019 of more than 500 mPas and less than 4500 mPas, and a fusion enthalpy measured according to ISO 11357-3 of more than 20 J / g and less than 35 J / g.
2. 2. Silane-modified polypropylene copolymer according to claim 1, characterized in that the melt viscosity, measured according to DIN 53019, is 10-50% of the viscosity of the original unmodified polypropylene copolymer.
3. 3. The silane modified polypropylene copolymer according to claim 1 or 2, characterized in that the polypropylene copolymer backbone has a weight average molecular weight, measured according to ISO 16014-1, of more than 10,000 g / mol and less than 30,000 g / mol.
4. Silane modified polypropylene copolymer according to any one of claims 1 to 3, characterized in that the polydispersity index (PDI), measured according to ISO 16014-1, is less than 2.5, said PDI being higher than the value of the unmodified polypropylene copolymer as a result of the grafting.
5. 5. The silane-modified polypropylene copolymer according to claim 1, characterized in that it has a softening point of 85 to 95° C., measured according to ASTM D3104.
6. 0.900 g / cm3 measured according to ISO 1183-3:1999 3 6. The silane-modified polypropylene copolymer according to claim 1, characterized in that it has a density of more than
7. 13 The silane-modified polypropylene copolymer according to any one of claims 1 to 6, characterized in that the mm triad of the propylene fraction confirmed by C-NMR is 90 mol% or less and the rr triad is at least 5 mol%.
8. The native reactants are 13 The silane-modified polypropylene copolymer according to any one of claims 1 to 7, characterized in that the propylene content confirmed by C-NMR is at least 60 mol%.
9. (a) providing an unmodified polypropylene copolymer; (b) adding a silane graft component and a free radical initiator; and (c) evaporating the excess monomer; The process for producing a silane-modified polypropylene copolymer according to any one of claims 1 to 8, characterized in that the melt viscosity measured at 170 ° C according to DIN 53019 is 50 to 90% lower than the viscosity of the original unmodified polypropylene copolymer and the PDI measured according to ISO 16014-1 is at least 20% higher due to the graft reaction.
10. 10. The process according to claim 9, wherein the unmodified polypropylene copolymer has a melt viscosity, measured according to DIN 53019 at 170°C, of 500 to 7000 mPas and a melt enthalpy, measured according to ISO 11357-3, of 30 to 55 J / g.
11. A hot melt adhesive formulation comprising the silane modified polypropylene copolymer according to any one of claims 1 to 8 and one or more base polymers selected from the group consisting of unmodified polyolefins and unmodified thermoplastic styrene block copolymers (TPE-S), wherein these components together represent at least 50% by weight and the silane modified polyolefin represents no more than 30% by weight, based on the total weight of the hot melt adhesive formulation.
12. 12. The hot melt adhesive formulation according to claim 11, characterized in that it has a melt viscosity, measured according to DIN 53019 at 170° C., of less than 5000 mPas and a tensile strength, measured according to DIN EN ISO 527-3, of at least 4 MPa.
13. 13. A hot melt adhesive formulation according to claim 11 or 12, characterized in that it comprises less than 35 wt.-% of a tackifier, based on the total weight of the hot melt adhesive formulation.
14. 14. The hot melt adhesive formulation according to any of claims 11 to 13, characterized in that it comprises 40 to 80 wt. % of said base polymer, 10 to 30 wt. % of said silane modified polypropylene copolymer, and 10 to 30 wt. % of a tackifier, based on the total weight of the hot melt adhesive formulation.
15. 15. The silane modified polypropylene copolymer according to any of claims 1 to 8 or the hot melt adhesive formulation according to any of claims 11 to 14, characterized in that the silane modified polypropylene copolymer or the hot melt adhesive formulation comprises 0.1 to 1 wt.-% of crosslinking accelerator, based on the total weight of the mixture of the silane modified polypropylene copolymer and the crosslinking accelerator or the hot melt adhesive formulation.
16. Use of a silane modified polypropylene copolymer according to any of claims 1 to 8 or a hot melt adhesive formulation according to any of claims 11 to 15 for bonding substrates.
Citation Information
Patent Citations
Modified polyolefin waxes
DE10338344A1
Reactive polyolefin hot-melt adhesive with lower reactivation temperature and use thereof in deep draw vacuum lamination
EP3287276A1
Silane-modified polyolefins with a high degree of functionalization
JP2012500292A
Crosslinkable propylene polymer composition
JP2020521832A
Silane-modified polypropylene, silane-modified polypropylene composition, silane crosslinked polypropylene, and molding including the same, crosslinked molding, 3D network fiber aggregate, and crosslinked molding of 3D network fiber aggregate
JP2023128806A
